The Utilization of the Environment as a Medium Instruction by Physical Education Teacher in the Coastal - Nurzaman, Umar (Department of Physical Education, Sport, Health and Recreation, 2018)
The purpose of this research is to know the types and ways to utilize the environment as a medium of learning from junior high school teachers in the coastal area of Kebumen Regency. This research method using qualitative research approach with data technique using interview technique, observation, and documentation.The research instrument uses interview guides and photo documentation. The results of environmental research are used as a place of learning in the coastal area Kebumen District, village buildings, beaches, and roads around the school. The environment used as learning media for Physical Education consists of paper assignment, modification of ball from coconut husk, perforated vessel made from used bucket, paint bucket cover and wood board for supporting learning. The conclusion of this research is the teacher of the coastal area surveyed Kebumen uses various ways to utilize the environment as a place of learning and learning media such as field to learn the big ball game and small ball game, while beach and school access road to learning athletics.